Analyzing the Impact of Coffee Company’s Marketing Campaigns and Brand Awareness on Consumer Purchase Intention - Gadi Dung Paul; Chaleeda A/P Perak Kerof; Ang Hui Xin; Andek Farzana Binti Andek Mohd Yasin; Chen Jingrui; Akanksha Chauhan; Ng Hee Song (Journal of The Community Development in Asia, 2024)
Starbucks, an established company in the worldwide coffee sector, makes huge investments in creative marketing techniques to attract and keep consumers. This study aimed to investigate the impact of marketing campaigns and brand awareness on consumer purchasing intentions in Malaysia and India, focusing on Starbucks as a case study. A quantitative research approach was employed, using an online survey distributed via Google Forms to 150 Starbucks consumers across both countries. The results revealed that marketing campaigns have a substantial impact on consumer purchase intentions, with a beta value of 0.889 (*p 0.001), explaining 84.4% of the variance. In contrast, brand awareness, while positively related, had a lesser impact (beta = 0.068, p 0.05). These findings suggest that Starbucks' success lies in its ability to create marketing content that resonates deeply with consumer values and lifestyles, driving stronger purchase intentions. The study underscores the importance of targeted, value-aligned marketing strategies that foster emotional engagement and highlights the need for brands to focus on meaningful consumer interactions to sustain and grow purchase intentions